ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN TAHUN 2017-2020 - Novie Al Muhariah; Andri Irawan; Adela Yolanda (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This research is entitled The Analysis of Factors Influencing Regency/City Workforce Absorption in South Sumatra Province in 2017-2020. The main objective of this study is to determine the influence of minimum wage, GRDP and capital expenditure on employment in South Sumatra Province. The method used in this study is Panel Data Regression Analysis with the Random Effect Model method. This study combines time series and cross section data, namely 2017-2020 and 17 districts/cities in South Sumatra Province, then for the data processing and analysis using the help of EView's 12 program. Based on the results of the research analysis, it can be concluded that the variables of minimum wage, GRDP and capital expenditure simultaneously have a significant influence on employment. While partially, the minimum wage variable has a negative and insignificant influence on employment, the GRDP variable has a positive and significant influence on employment, and the capital expenditure variable has a negative and significant influence on employment. The value of the coefficient of determination (Adjusted R2) shows that the contribution of the minimum wage, GRDP and capital expenditure variables is 40.90%, while 59.10% is influenced by other variables not included or variables that are not examined in this research model.